2022
DOI: 10.1177/15593258221131462
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin Inhibitor Isolated From Glycine max (Soya Bean) Extraction, Purification, and Characterization

Abstract: The current study aims to isolate, purify, and characterize the trypsin inhibitor protein from seeds of soya beans, scientifically known as Glycine max. Its seeds were ground, and the powder was soaked several times using n-hexane. It was added to phosphate buffer saline (PBS) followed by filtration and centrifugation of the PBS dissolved extract. The supernatant was subjected to ammonium sulfate precipitation and about six fractions, 30% to 80% were prepared. The centrifuged pellets obtained from each fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
0
0
Order By: Relevance
“…It was found that ultrafiltration did not completely remove salt from the Membrane dialysis has also been used in protein purification to improve separation efficiency and yield. In a study on protein extraction from soybean, Khan et al [103] used membrane dialysis to remove the salt from the trypsin inhibitor protein extract. The supernatant from protein extraction was subjected to centrifugation followed by ammonium sulfate precipitation.…”
Section: Diverse Applications Of Ultrafiltration In Protein Processingmentioning
confidence: 99%
“…It was found that ultrafiltration did not completely remove salt from the Membrane dialysis has also been used in protein purification to improve separation efficiency and yield. In a study on protein extraction from soybean, Khan et al [103] used membrane dialysis to remove the salt from the trypsin inhibitor protein extract. The supernatant from protein extraction was subjected to centrifugation followed by ammonium sulfate precipitation.…”
Section: Diverse Applications Of Ultrafiltration In Protein Processingmentioning
confidence: 99%